The operation of a novel optically modulated vertical-cavity semiconductor optical amplifier with wavelength converting functionality - Wah, J. Y.; Boland-Thoms, A.; Balkan, N. (2005)
We present initial results from a novel integrated vertical cavity semiconductor optical amplifier (VCSOA) and wavelength converter. The device can simultaneously emit and detect light. This feature makes it possible to integrate the wavelength conversion into the device. Also by incorporating a 1 lambda cavity active region sandwiched between a low reflectivity top mirror and a high reflectivity bottom mirror, the current device works as a VCSOA in reflection mode. The active cavity region consists of a simple p-i-n AlGaAs/GaAs/AlGaAs heterojunction. The device can be electrically and optically pumped. In the electrically pumped case, it provides an additional gate for optical modulation in the absorption section. in this work, we present the reflectivity spectrum of the VCSOA structure and demonstrate the operation of the device as an electrically pumped VCSOA in reflection mode. Carrier dynamics of the device are also illustrated through a three-dimensional energy band profile. (c) 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim